I Am a Mystery to Myself. Issue 4 (December 2017) - Miller, Joel
Abstract Throughout my lifetime I have had a vague sense of my identity. There were no distinct memories or stories from my childhood and adolescence to provide me with the recognition, much less an appreciation, for who I was in the world. It wasn't until I entered psychotherapy that revelations about my family life came into understanding. This was not from any recollecting of actual events but from the indirect observations of families where being engaged with each other had occurred. Through psychoanalysis, reading a variety of psychoanalytic thinkers, and by taking up my own writing I was encouraged to discover myself, even at the cost of the sorrow of never having that encouragement in growing up, the cost that comes with the exploration. Where no childhood home was to be found a new one was to be created instead.